SIMULATIONS OF SEISMIC ACTIVITY IN THE CORINTH GULF, GREECE, FAULT SYSTEM - Console, R.; Carluccio, R.; Papadimitriou, E.; Karakostas, V. (Bulletin of the Geological Society of Greece, 2016)
The characteristic earthquake hypothesis is not strongly supported by observational data because of the relatively short duration of historical and even paleoseismological records. For instance, for the Corinth Gulf Fault System (CGFS), historical information on strong earthquakes exist for at least two thousand years, but they can be considered complete for M > 6.0 only for the latest 300 years, and therefore only few characteristic earthquakes are reported for individual fault segments. The use of a physics-based earthquake simulator has allowed the production of catalogues lasting 100,000 years and containing more than 500,000 events of magnitudes > 4.0. Our simulation algorithm is based on several physical elements, such as an average slip rate due to tectonic loading for every single segment in the investigated fault system, the process of rupture growth and termination, and interaction between earthquake sources, including small magnitude events. The application of our simulation algorithm to the CGFS provided realistic features in time, space and magnitude behaviour of the seismicity. These features include longterm periodicity of strong earthquakes, short-term clustering of both strong and smaller events, and a realistic earthquake magnitude distribution departing from the Gutenberg-Richter distribution in the moderate and higher magnitude range.